Respons Singkat dan Makna Tersirat: Analisis Pragmatik dalam Komunikasi Teks Digital di Sosial Media WhatsApp - Aini Dhuha Hidayah; Winda Puji Lestari (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study explores the implicit meanings contained in short WhatsApp responses such as “yes,” “okay,” and “later,” analyzed through a pragmatic perspective emphasizing speech acts and conversational implicature. Using a qualitative descriptive approach, the research examines how contextual factors, relational dynamics, and digital cues like emojis or punctuation influence interpretation. The findings reveal that identical lexical expressions may convey varying illocutionary forces depending on tone, relationship closeness, and situational background. These differences often lead to misunderstandings or altered emotional perceptions in digital communication. The study highlights the importance of pragmatic awareness in online interaction to enhance clarity and maintain interpersonal harmony. It also contributes to the growing body of digital pragmatics research by demonstrating how brief text messages can carry complex social meanings that extend beyond their literal form